Konsep Eksosistem Pendidikan Merdeka: Perspektif Filosofis dan Praksis Najelaa Shihab - Indah Solekhah Candra; Masduki Asbari; Putri Ramadhani Rozikin (AGUSPATI RESEARCH INSTITUTA, 2023)
This study aims to describe the concept of the Independent Education ecosystem in Learning from Najelaa Shihab's perspective. This study report uses a descriptive qualitative method by taking notes because the data source was obtained by listening to oral narratives from the Bukalapak Wyang YouTube channel entitled